RUSSIAN FEDERATION GEO-ECONOMIC IMPACT AND POLITICAL RELATIONSHIP IN SHANGHAI COOPERATION ORGANIZATION AND ITS INFLUENCE IN THE ENERGY MARKET - Ahadi, Navidreza; Deebhijarn, Samart; Sornsaruht, Puris; Taghipour, Amirhossein; Mohammadi, Negar; Lotfian, Ali (PEOPLE: International Journal of Social Sciences, 2015)
This study is in regards to Russia Geo-economic interest and influence in Shanghai Cooperation Organization and the importance of SCO as a sufficient Eurasian organization’s leadership in energy market and the prospective of Russia to affect the energy market and energy reserve as a major authority within the organization.